E-Commerce and Luxury - From the Perspective of Female German Customers - Jens K. Perret; Carmen Horn; Lina Holthaus (Marketing Review St.Gallen, 2022)
A study of established and up-and-coming female luxury consumers reveals that in both groups there is some antipathy against the increasing digitalization of luxury brands since they expect a loss in exclusiveness. This is particularly significant in the case of Chanel, where the antipathy against digitalization is more pronounced.
Keywords: 650